OPTIMALISASI KESEJAHTERAAN MASYARAKAT DESA CIKONENG MELALUI PEMBERDAYAAN PERTANIAN - Rodiah Musyarofah, Nurul; Tripuspita, Neneng; Kusyadi, Yudi (STKIP Pasundan, 2025)
This research examines the role of the Cikoneng Village government in community empowerment in rice farming to optimize the welfare of the village community. A descriptive qualitative method was used with data collection techniques through observation, interviews, and documentation. Informants included village government officials, farmers, and community leaders. The results showed that empowerment programs, such as counseling, training, provision of superior seeds, and agricultural equipment assistance, improved farmers' knowledge, skills, and productivity in rice farming. Obstacles include budget constraints, limited human resources, and inadequate agricultural infrastructure. Nonetheless, the implementation of this policy had a positive impact on community welfare by increasing farmers' income. This research suggests increasing community participation, alternative funding sources, developing human resources, and optimizing coordination with related institutions to optimize empowerment.